Sustaining Improvements in CLABSI Reduction in a Pediatric Cardiac Intensive Care Unit. Issue 4 (23rd July 2022) - Gauntt, Jennifer; Brandt, Sarah; Dolan, Kevin; Manley, Jaime; Tyner, Roxann; Beauseau, Wendi; Simsic, Janet M.
Abstract : Introduction: Central line-associated bloodstream infections (CLABSIs) are preventable events that increase morbidity and mortality. The objective of this quality project was to reduce the incidence of CLABSIs in a pediatric cardiothoracic intensive care unit. Methods: Institutional review of an unacceptably high rate of CLABSIs led to the implementation of 4 new interventions. These interventions included: the use of sequential cleaning between line accesses, Kamishibai card audits, central line utilization and entry audits, and proctored simulation of line access. Results: There was a reduction in CLABSI rate from 1.52 per 1, 000 central line days in 2018 to 0.37 per 1, 000 central line days in 2020 and 0.32 in 2021. Additionally, central line days per 100 patient days decreased from 77 to 70 days over the study period. The cardiothoracic intensive care unit went 389 days without a CLABSI from October 2020 to November 2021. Conclusions: Implementation of multiple interventions led to a successful reduction in the incidence of CLABSIs in our unit, with a sustained reduction over 1 year.